DILEMMA AND HABITUS AS A BOUNDED RATIONALITY IN THE USE OF THE HUMAN DIMENSION IN MARINE SPATIAL PLANNING (MSP) - Ramadhan, Andrian
Considering the human dimension in MSP has been widely suggested to achieve social sustainability of coastal and marine use. However, many MSP practices do not consider the human dimension properly. Whereas ignoring this dimension can result in the threat of losing the heritage, livelihoods, and culture of coastal communities that have relied on the marine environment. This study explores the dilemmas faced when using the human dimension and tries to understand how decisions are made amid a dilemma using the habitus theory. Habitus’ theory complements academic arguments regarding the use of the human dimension, which so far only emphasizes objective aspects such as the structure of power and the capacity of the available resources. In this context, institutional habitus, influenced by subjective disposition and objective structure, will play an important role in framing the rationality of decision-making. The method used in this study is qualitative due to its ability to gather explanatory and naturalistic information. This study employs several data collection techniques as a form of triangulation, such as observation and interviews. The strategy used is a case study to obtain in-depth information about the human dimension of dilemma and the bounded of MSP rationality in a specific context. The results of the study indicate that the use of human dimensions is constrained by three factors: the dilemma posed by the arena, institutional capital ownership, and institutional habitus. These limitations give rise to three decision-making types for the use of human dimensions in MSP: adoption, limited adoption, and neglect. The resulting constraints impede the achievement of the goal of using human dimensions. However, the post-zonation period has seen the emergence of more informal community participation, with the community heavily involved in supervising, socializing, and developing community-based regulations in utilization zones. This flexible approach to zonation implementation allows for basic community interests to be negotiated even when they are disrupted. For example, fishing for daily needs can still be tolerated, even when carried out in forbidden zones such as protection and core zones. Persuasive approaches from community leaders who partner with BTNKJ have proven effective in increasing community compliance, although they require a long time to succeed. The distribution of benefits generally favors the local community, as evidenced by the utilization of coastal and marine areas for fishing and marine tourism. This outcome is due to the initiatives of local actors supported by BTNKJ in protecting the community's interests in these two types of utilization. Conversely, shrimp farming activities pose a threat to the community, as they result in more losses than benefits..